Contract goat farming: an emerging model for livelihood generation among resource poor farmers of western Odisha - SAHOO, CHINMAYA KUMAR; TIWARI, RUPASI; ROY, RAKESH; BHARTI, P K; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2016)
The present study was taken up with the objective to find out the pattern of contract goat farming (CGF) in western Odisha. Data were collected through personal interview from 60 contract goat farmers for pattern and practices in CGF and 20 key informants for understanding the existing models in CGF in the study area. The study showed that there were a number of models of CGF existing in the study area based on provision of input, services and marketing of kids. All of these models revealed that these types of contract goat farming were acting as a source of income and employment for the resource poor farmers and rural youth. The study showed that the traditional goat farming over the years had taken a commercial outlook in the form of contract goat farming. Though it was informal but the services and marketing strategies to be provided were clearly defined in various models of the CGF before entering into contract. The various models revealed an equal distribution of profit among the two parties, which was the basis of a strong bonding and a long term business venture. The CGF operational in western Odisha suggest an excellent model of employment and income generation for resource poor rural people and educated youth. In fact these models if taken up on a large scale in areas with similar agro-climatic zones can definitely boost the livelihood security among the educated unemployed youth and poor farmers.